Application Of Tourism Recommendations At Tanggamus Based On Android Using Figma Model - Genta Nirvana; Trisnawati Trisnawati (International Journal of Artificial Intelligence and Robotic Technology (IJAIRTec), 2022)
Tourism in Indonesia is currently increasing in number and attractive, especially in the Tanggamus Regency area. Tanggamus Regency is a district located in Lampung Province, this district has an area of 2,855.46 km 2 . Tanggamus Regency also has a variety of tourism that can be explored. However, there are still many ordinary people who do not know clear information about these tourist objects. Therefore, it is necessary to have an information system that can help the community in finding information about the tourist objects they want to visit, especially in the Tanggamus Regency area. In this study, two data collection methods were used, namely observation and literature. In addition, the design model used in this study is the waterfall method which consists of requirements, design, implementation, verification and maintenance. This research will produce a tourism recommendation mobile application interface in Tanggamus Regency, which in making the interface design uses figma. In the interface, the sections that are displayed include the initial display, the login display, the registration display, and the appearance of a tourist attraction.